MEDICINAL PLANTS USED IN CHILE FOR THE TREATMENT OF HYPERTENSION AND MOUNTAIN SICKNESS - MartÃnez, José L.; Calvo, Carlos A.; Laurido, Claudio (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
Hypertension is one of the principal health problems in the society, and an important cause of cardiovascular death in the world. In this work, we present a review of 16 native Chilean plants used in traditional medicine to treat hypertension or mountain sickness, recompiled from manuscripts (books and articles) published regarding medicinal plants. The purpose of this publication is to be a bibliographical source for the eventual study of the active principles contained in the medicinal plants, and the study of the physiological mechanisms underlying such activity, i.e. calcium antagonists and others.